Impact of land use on Histosols properties in urban agriculture ecosystems of Rio de Janeiro, Brazil - Otavio Augusto Queiroz dos Santos; Eduardo Carvalho da Silva Neto; Andrés Calderín García; Hugo de Souza Fagundes; Yan Vidal de Figueiredo Gomes Diniz; Robert Ferreira; Marcos Gervasio Pereira (Revista Brasileira de Ciência do Solo, 2020)
ABSTRACT Histosols provide several ecosystem services, related mainly to their reserves of carbon and nitrogen. Management practices in these soils can increase the mineralization of organic matter and contribute to the emission of greenhouse gases. This study aimed to investigate the effect of tillage with plowing and drainage on Histosol properties in three land use systems located in the municipality of Rio de Janeiro, Brazil. Three areas subjected to different land use systems over the last twenty years were chosen: Area 1, secondary forest with natural regeneration; Area 2, conventional tillage of cassava with plowing; and Area 3, intercropped coconut + cassava with an artificial drainage system. The chemical characterization, von Post scale of organic matter decomposition, percentage of rubbed fiber, organic matter, percentage of mineral material, bulk density, electrical conductivity, soluble phosphate, total organic carbon (TOC) and nitrogen (NT), organic carbon fractions, and C and N stocks were analyzed. Our results showed the critical, nearly irreversible effects of agricultural practices comprising drainage and plowing of the soil. Over twenty years, in Area 2, the TOC and NT values decreased by 33 and 20 %, respectively in the histic horizon, and by about 17 and 8 %, respectively in the gley horizon. In Area 3, the TOC and NT values decreased by 31 and 18 %, respectively, in the histic horizon, and by 27 and 21 % in the gley horizon. Our findings also showed that the loss of C is related to the labile organic carbon, which is more sensitive to environmental changes, even at deeper depths. The plowing of the soil decreases the organic matter content due to the accelerated oxidation of organic matter, increasing the bulk density. Drainage, besides the loss of organic matter by subsidence, promotes the sulfidization of the soil with a high content of SO42-, due to the oxidation of soil materials containing sulfides.